Salinity Tolerance Characteristics of Marginally Located Rice Varieties in the Northernmost Rice-Growing Area in Europe - Árpád Székely; Tímea Szalóki; János Pauk; Csaba Lantos; Marks Ibadzade; Mihály Jancsó (Agronomy, 2022)
Detailed experiments were performed to investigate the effects of the marginal cultivation of temperate japonica rice on salinity tolerance in different developmental stages and to detect new genetic resources for further research and breeding projects. Eight rice varieties were screened for salinity tolerance in a greenhouse at two developmental stages. During seedling-stage screening, stress was induced with a 12 dS m−1 NaCl solution. For reproductive-stage analysis, we applied continuous salinity stress (8.39 dS m−1 of soil extract at 25 °C (EC25)). We compared the marginal rice genotypes (japonica_1) to widely grown controls (those being Mediterranean japonica genotypes, referred as the japonica_2 group, which also included one indica genotype). Without stress, marginally cultivated genotypes had significantly higher potassium storage capacity (406 µmol g−1) in flag leaves than did japonica_2 (347) or indica (267). Moreover, the seeds contained twice as much sodium (5.27) as did the others (2.19 and 2.00). Based on root-to-grain allocation, we identified two sodium excluders (‘Dular’ and ‘Dáma’) and six includers under constant salinity stress. Among the includers, we found that ‘M488’ had extremely high sodium concentration in both the flag leaves (250.54 µmol g−1) and the grains (13.57 µmol g−1). Rice varieties bred for the edge of their habitat show special physiological patterns. The differences are mainly manifested as lower levels of antioxidant pigments, higher amounts of potassium in flag leaves, and higher sodium levels in grains under normal conditions. With the onset of stress, higher tillering ability, enhanced antioxidant pigment synthesis, and rapid potassium translocation from the root are the key mechanisms which help the plants to avoid serious damage caused by salinity.